2015
DOI: 10.1021/jacs.5b09487
|View full text |Cite
|
Sign up to set email alerts
|

Desymmetrized Vertex Design for the Synthesis of Covalent Organic Frameworks with Periodically Heterogeneous Pore Structures

Abstract: Two novel porous 2D covalent organic frameworks (COFs) with periodically heterogeneous pore structures were successfully synthesized through desymmetrized vertex design strategy. Condensation of C(2v) symmetric 5-(4-formylphenyl)isophthalaldehyde or 5-((4-formylphenyl)ethylene)isophthalaldehyde with linear hydrazine linker under the solvothermal or microwave heating conditions yields crystalline 2D COFs, HP-COF-1 and HP-COF-2, with high specific surface areas and dual pore structures. PXRD patterns and compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 43 publications
2
111
0
6
Order By: Relevance
“…[4e] In a later work, COFs having periodically heterogeneous pore structures were synthesized by using a desymmetrized vertex design strategy. [11] Recently, a library of about fifty new COFs of symmetric and asymmetric singular-pore structure was reported. This library was accessed through a mixed monomer synthesis approach where subunits of a similar symmetry but different dimensions resulted in pores of different aspect ratios.…”
Section: Introductionmentioning
confidence: 99%
“…[4e] In a later work, COFs having periodically heterogeneous pore structures were synthesized by using a desymmetrized vertex design strategy. [11] Recently, a library of about fifty new COFs of symmetric and asymmetric singular-pore structure was reported. This library was accessed through a mixed monomer synthesis approach where subunits of a similar symmetry but different dimensions resulted in pores of different aspect ratios.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the effect of global warming, many porous materials, such as metal organic frameworks (MOFs) [5][6][7][8][9], porous co-ordination polymers [10,11], porous carbons [12][13][14][15][16], porous organic polymers (POPs) and covalent organic frameworks (COFs) [17][18][19][20], have been investigated for CO 2 storage. In recent years, many amine functionalized or nitrogen-rich porous materials were found to show good CO 2 adsorption properties because of the existence of strong interactions between the nitrogen functionality and CO 2 molecules [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However,e ach of these two strategies theoretically can lead to two types of COFs with different topological structures. [38] This drawback prevents unambiguous structural prediction of heteropore COFs from the structures of their building blocks and decreases the control over the construction of heteropore COFs. The previous studies have indeed revealed that, although the combination of tetraphenylethene-based D 2h -symmetrical monomers and linear linkers resulted in dual-pore COFs, [34][35][36][37] the formation of single-pore COFs was also observed when building blocks having the same symmetry but different structures were used.…”
Section: Introductionmentioning
confidence: 99%